Khataman Ṣaḥīh Bukhārī by PCNU Jombang (A Study of Living Hadith) - Nursyahbani, Iqbal; Junianto, Viki; Khamim, Khamim; Salsabila, Maulana Thalia (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
This research aims to analyze the social actions that occur during the Ṣaḥīh Bukhārī khatam event organized by the Jombang branch of Nahdlatul Ulama (PCNU). The study adopts Max Weber's perspective on social action as its analytical approach, using four of his theories: traditional, affective, rationality, and value orientation. The research methodology used is qualitative, with interviews as the data collection method. Additionally, a literature review is conducted to uncover historical data on the tradition of khatam Ṣaḥīh Bukhārī in Islam and the opinions of scholars (ulama). The research findings indicate that the Ṣaḥīh Bukhārī khatam activities of PCNU Jombang continue to exist due to four factors. First, these activities are a manifestation of the respect and preservation of traditions practiced by scholars in Islam and the NU organization itself. Second, the activities can evoke emotional responses from the participants because they share a common goal and are influenced by the presence of respected religious leaders (Kyai) who contribute to the emotional atmosphere. Third, the activities are consistently carried out because the participants possess the capacity to engage in them rationally. Fourth, all participants believe that these activities hold significant and beneficial values, which are highly anticipated by everyone involved. Penelitian ini bertujuan untuk menganalisis tindakan sosial yang terjadi dalam acara Khataman Ṣaḥīh Bukhārī yang diselenggarakan oleh Pengurus Cabang Nahdlatul Ulama (PCNU) Jombang. Penelitian ini mengadopsi perspektif Max Weber tentang tindakan sosial sebagai pendekatan analisisnya dengan empat teorinya yaitu, tradisional, afektif, rasionalitas, dan orientasi nilai. Metode penelitian yang digunakan untuk mengumpulkan data adalah metode kualitatif dengan wawancara dan dokumentasi. Selain itu, kajian literatur juga dilakukan untuk mengungkap data sejarah dari tradisi Khataman kitab Ṣaḥīh Bukhārī dalam Islam dan pendapat ‘ulama. Hasil penelitian menunjukkan bahwa kegiatan Khataman Ṣaḥīh Bukhārī PCNU Jombang selalu eksis karena empat faktor. Pertama, kegiatan ini merupakan wujud dari penghormatan dan pelestarian tradisi-tradisi yang dilakukan ‘Ulama dalam Islam dan organisasi NU sendiri. Kedua, kegiatan ini dapat menyentuh rasa emosional para pesertanya karena memiliki sebuah tujuan yang sama serta adanya figur kyai yang juga berperan dalam membentuk rasa emosional tersebut. Ketiga, kegiatan ini selalu dilaksanakan karena secara rasional para pesertanya memiliki kapasitas dalam menjalankannya. Keempat, kegiatan ini diyakini oleh semua pesertanya memiliki nilai-nilai baik yang sangat bermanfaat dan sangat diharapkan oleh semua peserta.